(untitled) (British Journal of Global Ecology and Sustainable Development, 2023)
In Karmana District of Navoi region there are many historical monuments, sacred steps. For example, Mir Sayyid Bahrom, Rabati Malik Caravanserai mausoleums. In this article, I will try to provide information about the importance of historical monuments located in the Karmana district.